Underwater LiDAR Signal Processing for Enhanced Detection and Localization of Marine Life - Dubrovinskaya, Elizaveta; Dalgleish, Fraser; Ouyang, Bing; Casari, Paolo (2018 OCEANS MTS IEEE Kobe Techno Oceans (OTO), 2018)
The in situ detection, recognition and tracking of marine animal species is a very important step of field research in the domains of, among others, biology and ecology. Still, the direct observation of marine wildlife through equipment operating in the visible light spectrum is often impaired by the challenging conditions offered by ocean waters, where light can be subject to scattering and attenuation phenomena due to the water turbidity. As the use of powerful lighting may prove ineffective and even induce behavioral changes in marine animals, the design of minimally or non-invasive observation instruments becomes particularly important. In this paper, we consider the serial Light Detection And Ranging (LiDAR) system under development at the Florida Atlantic University (FAU). This LiDAR design is based on inexpensive components and on low average power red lasers which are subject to significant attenuation in water, but are both eye-safe and invisible to marine life. Considering the challenge of detecting and evaluating the presence of marine wildlife, we present a full processing pipeline for LiDAR data, that includes water turbidity detection, non-gated backscattering compensation, contrast enhancement, and the construction of a three-dimensional model of the detected target. The pipeline is applied to a number of tank test data, under different turbidity conditions.